Situação endêmica da hanseníase em uma cidade do interior do Rio Grande do Sul - Andréia Rosane Moura Valim; Lia Gonçalves Possuelo; Marcelo Carneiro; Luciano Duro (Universidade de Santa Cruz do Sul, 2012)
The control ofleprosy is a public health priority, however, the lowprevalence in Rio Grande do Sul favoring underdiagnosis.The objective was to evaluate patients withleprosy during 1995 to 2005 in the city of Santa Cruzdo Sul, RS. Results: We performed a retrospectiveanalysis of 38 medical records and assessed the situationof 67 contacts. The mean age was 50.5 years,without gender dominance. The majority (87.2%)were Caucasian farmers with low education (74%).Multibacillary cases predominated (71.1%), clinicalform virchowiana (52%) and functional incapacitywas found in 36.8%. Only one contact with leprosywas identified. Conclusion: The control of a lowprevalence area should prioritize early detection,facilitating the prevention of disabilities.